The Research on Landscape Design Strategy of Xuzhou Mining Wastelands from the Perspective of Naturalism Aesthetics - Xing, Hongtao; Puntien, Pisit (Journal of Roi Kaensarn Academi, 2024)
With the continuous development of urban mineral resources, the ecology of mining areas has been seriously damaged, and the landscape design of mining wastelands has gradually received attention. To address this issue, the sample of this study is the landscape regeneration design of Xuzhou Anran Mountain abandoned quarry, this study aims to enhance the natural aesthetic value and beautiful ecological environment of the site through the sample. This study adopts a mixed research method: a combination of qualitative and quantitative methods, with qualitative research as the main focus, combined with questionnaires, interview records, data statistics, field research, case studies and other methods, to comprehensively analyze the development history, distribution and characteristics of the landscape of the mining wastelands in Xuzhou, and to summarize the aesthetic performance and design strategies of the naturist landscape. The goal of the study is to explore the performance of naturalistic aesthetic language in the landscape regeneration design of mining wastelands in Xuzhou. In order to balance the harmonious relationship between the natural landscape, ecological environment and tourists of mining wastelands. The results of the study show that (1) the development of the landscape of mining wastelands, experienced the germination, transformation and development period. (2) The distribution of mining wastelands in Xuzhou presents a “point-like” distribution. It is characterized by serious damage to natural ecology and scattered humanistic landscape. (3) The design strategy of the research theme is summarized by prioritizing the restoration of natural ecology, incorporating the language of natural aesthetics, and interacting with dynamic aesthetic elements. (4) Based on the profile and advantages of the sample site, this study proposes design inspiration, design concepts and objectives, analyzes the value of natural aesthetics of the quarry, and carries out a deeper dissection and validation of the sample under the guidance of naturalistic aesthetic theory. The results of the study help to promote the development of the region’s economy and ecological environment, and provide a theoretical basis and practical guidance for the design of natural aesthetics in abandoned landscapes in Xuzhou and other regions.